Bracing Timber‐glass‐façade | Feasibility studies, performance assessments and optimization. Issue 5 (22nd October 2018) - Fadai, Alireza; Rinnhofer, Matthias; Wagner, David
ABSTRACT: To introduce the research question a brief overview of existing computational models is given. Up till now, there is merely a guideline but no European standard for structural‐sealant‐glazing systems. Consequently, the focus will be on the experimental large‐sized specimens with load‐bearing adhesives, after that an optimized specimen based on them will be analyzed. This optimizations are just basis of theoretical considerations. The main aspect is to evaluate and interpret the deformation mechanisms over a long‐term observation period and unsteady climatic conditions. The feasibility studies, performance assessments and optimization of bracing timber‐glass‐composite (TGC)‐façades is a main component. Therefore, ideal four‐story buildings are exposed to horizontal wind force. To increase their stiffness a horizontal and vertical connection (coupling) between the TGC‐elements is analyzed. In addition to the commonly used silicone adhesive a stiffer epoxy is used as an alternative. In this way, it is also thinkable to reach higher stiffness. TGC‐façades should consequently replace the stiffening walls and take all the bracing function. To calculate their utilization and resistance, stress and stability analysis are required. Safety factors and strength values based on scientific knowledge are the basis for that. Finally, various component‐adaptations are carried out step by step. This illustrates the complex relationship in the stiffening behavior.